Aquila Optimizer: A novel meta-heuristic optimization algorithm. (July 2021) - Abualigah, Laith; Yousri, Dalia; Abd Elaziz, Mohamed; Ewees, Ahmed A.; Al-qaness, Mohammed A.A.; Gandomi, Amir H.
Highlights: Developed a novel optimizer inspired by the behavior of Aquila (AO). Tested AO against classical, CEC2017, CEC2019 test functions and engineering problems. Compared the AO to other similar optimization algorithms. Demonstrated effectiveness and superiority of the proposed algorithm. Abstract: This paper proposes a novel population-based optimization method, called Aquila Optimizer (AO), which is inspired by the Aquila's behaviors in nature during the process of catching the prey. Hence, the optimization procedures of the proposed AO algorithm are represented in four methods; selecting the search space by high soar with the vertical stoop, exploring within a diverge search space by contour flight with short glide attack, exploiting within a converge search space by low flight with slow descent attack, and swooping by walk and grab prey. To validate the new optimizer's ability to find the optimal solution for different optimization problems, a set of experimental series is conducted. For example, during the first experiment, AO is applied to find the solution of well-known 23 functions. The second and third experimental series aims to evaluate the AO's performance to find solutions for more complex problems such as thirty CEC2017 test functions and ten CEC2019 test functions, respectively. Finally, a set of seven real-world engineering problems are used. From the experimental results of AO that compared with well-known meta-heuristic methods, the superiority of the developed AO algorithm is observed. Matlab codes of AO are available at https://www.mathworks.com/matlabcentral/fileexchange/89381-aquila-optimizer-a-meta-heuristic-optimization-algorithm and Java codes are available at https://www.mathworks.com/matlabcentral/fileexchange/89386-aquila-optimizer-a-meta-heuristic-optimization-algorithm .